The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

The use of data for health and welfare management of farmed salmons in Norway, Scotland, and Ireland - Xiao Zhou; Annette S. Boerlage; Britt Bang Jensen; Kristine Gismervik; Victor H.S. Oliveira; Ian Hutchinson; Alison Burrell; David A. Graham; Charlotte Doidge; Jasmeet Kaler; Gerdien van Schaik; Michael Siegrist; et al. (Preventive Veterinary Medicine, 2025)

Carbon footprints of greenhouse gas mitigation measures for a grass-based beef cattle finishing system in the UK - Asma Jebari; Taro Takahashi; Michael R. F. Lee; Adrian L. Collins; Kevin Coleman; Alison Carswell; Carmen Segura; Laura Cardenas; Graham A. McAuliffe (The International Journal of Life Cycle Assessment, 2025)
Purpose Agri-food systems across the globe are faced with the challenge of reducing their supply-chain emissions of greenhouse gases (GHGs) such as nitrous oxide (N 2 O), carbon dioxide (CO 2 ), and methane (CH 4 ). For instance, 10% of the UK’s GHG emissions are generated by agriculture, and ~ 56% of these are generated by livestock production. Numerous mitigation measures are being proposed to reduce GHG emissions from ruminants (representing 70 to 80% of total livestock emissions), particularly from beef cattle (presenting 30–40% of total livestock emissions). Methods To explore such potential, first, a business-as-usual (BAU) partial cradle-to-finishing farmgate scale modelling framework was developed. The BAU systems (i.e. steady-state productivity based on primary data from the North Wyke Farm Platform) were built using ensemble modelling wherein the RothC process-based soil organic carbon (SOC) model was integrated into the life cycle assessment (LCA) framework to conduct a trade-off analysis related to mitigation measures applicable to the study system. Potential mitigation measures were applied to the BAU scenario. The interventions assessed included: (i) extensification; (ii) adopting anaerobic digestion technology; and (iii) the use of the nitrification inhibitor DCD and substitution of fertiliser nitrogen with symbiotically fixed nitrogen from legumes. Results The partial carbon footprint for 1 kg of beef liveweight gain leaving the farmgate could be reduced by 7.5%, 12%, or 26% by adopting nitrification inhibitors, white clover introduction (pending establishment success), and anaerobic digestion for manure management, respectively. Conclusions The findings highlight the importance of including emissions beyond the farmgate level to analyse the carbon footprint of different management scenarios in order to assess the sustainability of agri-food production systems.

Development and in-vitro assessment of novel oxygen-releasing feed additives to reduce enteric ruminant methane emissions - Alison Graham; Camilla Thorn; Michael McDonagh; Caroline O'Donnell; Stephen Nolan; Stuart F. Kirwan; Sandra O'Connor; Corine O. Nzeteu; Alejandra C.V. Montoya; Andrew Bartle; Alison Hall; Cathy Abberton; et al. (Science of The Total Environment, 2025)

Survey of foodborne pathogenic Vibrio species in commercial Tasmanian bivalve shellfish and predictors of risk at harvest - Valeria Anna Torok; Khandaker Rayhan Mahbub; Paul A. Grey; Graham Clive Fletcher; Alison R. Turnbull (International Journal of Food Microbiology, 2025)

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Bushfire exposure is associated with darker color of beef loin at grading - Melindee Hastie; Graham Hepworth; Alison Hillman; Caitlin Pfeiffer; Brendan Cowled; Robyn Warner (Livestock Science, 2024)

A multi-methods, multi-actor exploration of the benefits and barriers to milk recording on Irish farms using the COM-B model - Alison MG Burrell; Lorraine Balaine; Seán Clifford; Michelle McGrath; David A. Graham; Finola McCoy; Emma Dillon; Áine Regan (Preventive Veterinary Medicine, 2024)

Non-invasive methods of monitoring Fe3O4 magnetic nanoparticle toxicity in human liver HepaRG cells using impedance biosensing and Coherent anti-Stokes Raman spectroscopic (CARS) microscopy - Joel Kuhn; Alison McDonald; Cyril Mongoin; Graham Anderson; Guillemette Lafeuillade; Stephen Mitchell; Alistair P.D. Elfick; Pierre O. Bagnaninchi; Humphrey H.P. Yiu; Leonard J. Nelson (Toxicology Letters, 2024)

Acclimation of microbial communities to low and moderate salinities in anaerobic digestion - Claribel Buenaño-Vargas; M. Cristina Gagliano; Lara M. Paulo; Andrew Bartle; Alison Graham; H. Pieter J. van Veelen; Vincent O'Flaherty (Science of The Total Environment, 2024)

Occurrence and biomagnification of perfluoroalkyl substances (PFAS) in Lake Michigan fishes - Daniele A. Miranda; Alison M. Zachritz; Heather D. Whitehead; Shannon R. Cressman; Graham F. Peaslee; Gary A. Lamberti (Science of The Total Environment, 2023)

Using multi-platform LiDAR to guide the conservation of the world's largest temperate woodland - Tommaso Jucker; Carl R. Gosper; Georg Wiehl; Paul B. Yeoh; Nat Raisbeck-Brown; Fabian Jörg Fischer; Jason Graham; Helen Langley; William Newchurch; Alison J. O'Donnell; Gerald F.M. Page; Katherine Zdunic; et al. (Remote Sensing of Environment, 2023)

Bushfire exposure is associated with increased pH and dark-cutting in beef longissimus thoracis at grading - Melindee Hastie; Graham Hepworth; Alison Hillman; Brendan Cowled; Caitlin Pfeiffer; Robyn D. Warner (Meat Science, 2023)

Identification of genetic loci in lettuce mediating quantitative resistance to fungal pathogens - Harry Pink; Adam Talbot; Abi Graceson; Juliane Graham; Gill Higgins; Andrew Taylor; Alison C. Jackson; Maria Truco; Richard Michelmore; Chenyi Yao; Frances Gawthrop; David Pink; et al. (Theoretical and Applied Genetics, 2022)
Key message We demonstrate genetic variation for quantitative resistance against important fungal pathogens in lettuce and its wild relatives, map loci conferring resistance and predict key molecular mechanisms using transcriptome profiling. Abstract Lactuca sativa L. (lettuce) is an important leafy vegetable crop grown and consumed globally. Chemicals are routinely used to control major pathogens, including the causal agents of grey mould ( Botrytis cinerea ) and lettuce drop ( Sclerotinia sclerotiorum ) . With increasing prevalence of pathogen resistance to fungicides and environmental concerns, there is an urgent need to identify sources of genetic resistance to B. cinerea and S. sclerotiorum in lettuce. We demonstrated genetic variation for quantitative resistance to B. cinerea and S. sclerotiorum in a set of 97 diverse lettuce and wild relative accessions, and between the parents of lettuce mapping populations. Transcriptome profiling across multiple lettuce accessions enabled us to identify genes with expression correlated with resistance, predicting the importance of post-transcriptional gene regulation in the lettuce defence response. We identified five genetic loci influencing quantitative resistance in a F 6 mapping population derived from a Lactuca serriola (wild relative) × lettuce cross, which each explained 5–10% of the variation. Differential gene expression analysis between the parent lines, and integration of data on correlation of gene expression and resistance in the diversity set, highlighted potential causal genes underlying the quantitative trait loci.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Assembly and characterisation of a unique onion diversity set identifies resistance to Fusarium basal rot and improved seedling vigour - Andrew Taylor; Graham R. Teakle; Peter G. Walley; William E. Finch-Savage; Alison C. Jackson; Julie E. Jones; Paul Hand; Brian Thomas; Michael J. Havey; David A. C. Pink; John P. Clarkson (Theoretical and Applied Genetics, 2019)
Key message A unique, global onion diversity set was assembled, genotyped and phenotyped for beneficial traits. Accessions with strong basal rot resistance and increased seedling vigour were identified along with associated markers. Abstract Conserving biodiversity is critical for safeguarding future crop production. Onion ( Allium cepa L.) is a globally important crop with a very large (16 Gb per 1C) genome which has not been sequenced. While onions are self-fertile, they suffer from severe inbreeding depression and as such are highly heterozygous as a result of out-crossing. Bulb formation is driven by daylength, and accessions are adapted to the local photoperiod. Onion seed is often directly sown in the field, and hence seedling establishment is a critical trait for production. Furthermore, onion yield losses regularly occur worldwide due to Fusarium basal rot caused by Fusarium oxysporum f. sp. cepae . A globally relevant onion diversity set, consisting of 10 half-sib families for each of 95 accessions, was assembled and genotyping carried out using 892 SNP markers. A moderate level of heterozygosity (30–35%) was observed, reflecting the outbreeding nature of the crop. Using inferred phylogenies, population structure and principal component analyses, most accessions grouped according to local daylength. A high level of intra-accession diversity was observed, but this was less than inter-accession diversity. Accessions with strong basal rot resistance and increased seedling vigour were identified along with associated markers, confirming the utility of the diversity set for discovering beneficial traits. The onion diversity set and associated trait data therefore provide a valuable resource for future germplasm selection and onion breeding.

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

Functioning of Coastal River-Dominated Ecosystems and Implications for Oil Spill Response: From Observations to Mechanisms and Models - Adam Greer; Alan Shiller; Eileen Hofmann; Jerry Wiggert; Sally Warner; Sabrina Parra; Chudong Pan; Jeffrey Book; DongJoo Joung; Steven Dykstra; Jeffrey Krause; Brian Dzwonkowski; et al. (Oceanography, 2018)

Associations between lobster phyllosoma and gelatinous zooplankton in relation to oceanographic properties in the northern Gulf of Mexico - Adam T. Greer; Christian Briseño‐Avena; Alison L. Deary; Robert K. Cowen; Frank J. Hernandez; William M. Graham (Fisheries Oceanography, 2017)
Lobster phyllosoma are known to associate with large cnidarian medusae; however, direct quantitative observations are difficult because gelatinous zooplankton are extremely fragile, and the phyllosoma easily detach from their host when sampled by plankton nets. We provide the first large scale quantitative information of the distribution of this association using an in situ imaging system, with synoptic measurements of water column properties. All phyllosoma were identified as slipper lobsters ( Scyllarus chacei ) and were associated with previously unreported “hosts” such as small hydromedusae, doliolids, and siphonophores in the northern Gulf of Mexico. Along the shelf, phyllosoma were more likely to be present at greater depths and higher salinities. Approximately 30% of the 347 lobster phyllosoma imaged were attached to at least one gelatinous organism, and salinity and depth were positively related to the probability of attachment on 30 October, but did not show a significant relationship for the other days of sampling. Many of the phyllosoma were larger than the gelatinous organisms to which they were attached, and some gelatinous zooplankton showed damage likely from feeding by the phyllosoma. In this coastal environment, gelatinous zooplankton tended to be more abundant in the same offshore region where phyllosoma occurred, so these gelatinous “hosts” may provide a steady food supply in the more oligotrophic waters on the outer shelf. Similar complex interactions among zooplankton may influence the life histories of other species, hindering our ability to forecast ecosystem level processes until the population level consequences of species interactions are fully understood.

Manganese transport is essential for N 2 ‐fixation by Rhizobium leguminosarum in bacteroids from galegoid but not phaseoloid nodules - Graham Hood; Vinoy Ramachandran; Alison K. East; J. Allan Downie; Philip S. Poole (Environmental Microbiology, 2017)
Summary Rhizobium leguminosarum has two high‐affinity Mn 2+ transport systems encoded by sitABCD and mntH . In symbiosis, sitABCD and mntH were expressed throughout nodules and also strongly induced in Mn 2+ ‐limited cultures of free‐living cells. Growth of a sitA mntH double mutant was severely reduced under Mn 2+ limitation and sitA and mntH single mutants were more sensitive to oxidative stress. The double sitA mntH mutant of R. leguminosarum was unable to fix nitrogen (Fix ‐ ) with legumes belonging to the galegoid clade ( Pisum sativum , Vicia faba and Vicia hirsuta ). The presence of infection thread‐like structures and sparsely‐packed plant cells in nodules suggest that bacteroid development was blocked, either at a late stage of infection thread progression or during bacteroid‐release. In contrast, a double sitA mntH mutant was Fix + on common bean ( Phaseoli vulgaris ), a member of the phaseoloid clade of legumes, indicating a host‐specific symbiotic requirement for Mn 2+ transport.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Sexual response of male Drosophila to honey bee queen mandibular pheromone: implications for genetic studies of social insects - Justin R. Croft; Tom Liu; Alison L. Camiletti; Anne F. Simon; Graham J. Thompson (Journal of Comparative Physiology A, 2017)

Mainstreaming the social sciences in conservation - Nathan J. Bennett; Robin Roth; Sarah C. Klain; Kai M. A. Chan; Douglas A. Clark; Georgina Cullman; Graham Epstein; Michael Paul Nelson; Richard Stedman; Tara L. Teel; Rebecca E. W. Thomas; Carina Wyborn; et al. (Conservation Biology, 2017)
Despite broad recognition of the value of social sciences and increasingly vocal calls for better engagement with the human element of conservation, the conservation social sciences remain misunderstood and underutilized in practice. The conservation social sciences can provide unique and important contributions to society's understanding of the relationships between humans and nature and to improving conservation practice and outcomes. There are 4 barriers—ideological, institutional, knowledge, and capacity—to meaningful integration of the social sciences into conservation. We provide practical guidance on overcoming these barriers to mainstream the social sciences in conservation science, practice, and policy. Broadly, we recommend fostering knowledge on the scope and contributions of the social sciences to conservation, including social scientists from the inception of interdisciplinary research projects, incorporating social science research and insights during all stages of conservation planning and implementation, building social science capacity at all scales in conservation organizations and agencies, and promoting engagement with the social sciences in and through global conservation policy‐influencing organizations. Conservation social scientists, too, need to be willing to engage with natural science knowledge and to communicate insights and recommendations clearly. We urge the conservation community to move beyond superficial engagement with the conservation social sciences. A more inclusive and integrative conservation science—one that includes the natural and social sciences—will enable more ecologically effective and socially just conservation. Better collaboration among social scientists, natural scientists, practitioners, and policy makers will facilitate a renewed and more robust conservation. Mainstreaming the conservation social sciences will facilitate the uptake of the full range of insights and contributions from these fields into conservation policy and practice.

The effect of adenosine monophosphate deaminase overexpression on the accumulation of umami-related metabolites in tomatoes - Bee Lynn Chew; Ian D. Fisk; Rupert Fray; Gregory A. Tucker; Zsuzsanna Bodi; Alison Ferguson; Wei Xia; Graham B. Seymour (Plant Cell Reports, 2017)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

How flies respond to honey bee pheromone: the role of the foraging gene on reproductive response to queen mandibular pheromone - Alison L. Camiletti; David N. Awde; Graham J. Thompson (The Science of Nature, 2014)

Assessment of the utility of dynamically-downscaled regional reanalysis data to predict streamflow in west central Florida using an integrated hydrologic model - Syewoon Hwang; Wendy D. Graham; Alison Adams; Jeffrey Geurink (Regional Environmental Change, 2013)

Microphytobenthic extracellular polymeric substances (EPS) in intertidal sediments fuel both generalist and specialist EPS‐degrading bacteria - Joe D. Taylor; Boyd A. McKew; Alison Kuhl; Terry J. McGenity; Graham J. C. Underwood (Limnology and Oceanography, 2013)
Microphytobenthic biofilms contain high concentrations of carbohydrate‐rich extracellular polymeric substances (EPS) that are important in sediment carbon cycling. Field measurements at two locations in the Colne Estuary, U.K., showed that a significant curvilinear relationship explained 50% of the variability in chlorophyll a and EPS content. Estimates of EPS production, based on field data and published rates of production by diatoms, revealed that EPS turnover of 52% to 369% over the tidal cycle was required to account for field standing stocks. We investigated EPS degradation in sediment slurries using purified 13 C‐EPS produced by the diatom Nitzschia tubicola . Although EPS constituted only 5% of the sediment dissolved organic carbon (DOC) pool, 100% of the added EPS was utilized within 30 h, before decreases in other sediment‐carbohydrate fractions and DOC concentrations. A general 13 C enrichment of phospholipid fatty acids (PLFAs), representative of Gram‐positive and Gram‐negative bacteria, occurred within 6 h, with the PLFAs a 15:0, i 15:0, and 18:1 ω 7c being highly enriched. The diatom PLFA 20:5 ω 3 had relatively low but significant 13 C enrichment. Stable isotope probing of 16S ribosomal ribonucleic acid (RNA‐SIP) at 30 h revealed 13 C‐enriched sequences from the diatom genus Navicula ; further evidence that diatoms assimilated the EPS, or EPS‐breakdown products, from other diatom taxa. RNA‐SIP also demonstrated a diverse range of highly 13 C‐enriched bacterial taxa, including a distinct subset (Alphaproteobacteria and Gammaproteobacteria) found only in the heavily labeled microbial assemblages. Thus, cycling of diatom EPS is rapid, and involves a wide range of microbial taxa, including some apparent specialists.

Use of genome-wide SNP homozygosity mapping in small pedigrees to identify new mutations in VSX2 causing recessive microphthalmia and a semidominant inner retinal dystrophy - Sibel Ugur Iseri; Alexander W. Wyatt; Gudrun Nürnberg; Christian Kluck; Peter Nürnberg; Graham E. Holder; Ed Blair; Alison Salt; Nicola K. Ragge (Human Genetics, 2010)

Habitat associations of the Small Red Damselfly (Ceriagrion tenellum) (De Villiers) in heathland in southern England (Zygoptera: Coenagrionidae) - Alison M. Strange; Geoffrey H. Griffiths; Sophie Hine; Kim Young; Graham J. Holloway (Journal of Insect Conservation, 2007)

Responses of Tuatara ( Sphenodon punctatus ) to Removal of Introduced Pacific Rats from Islands - DAVID R. TOWNS; G. RICHARD PARRISH; CLAUDINE L. TYRRELL; GRAHAM T. USSHER; ALISON CREE; DONALD G. NEWMAN; A. (TONY) H. WHITAKER; IAN WESTBROOKE (Conservation Biology, 2007)
Invasive mammalian predators such as rats are now widespread on islands, but hypotheses about their effects have rarely been tested. Circumstantial evidence from New Zealand indicates that, when introduced to islands, Pacific rats (Rattus exulans) have negative effects on endemic plants, invertebrates, birds, and reptiles, including the tuatara (Sphenodon punctatus). We tested the effects of Pacific rats on tuatara by comparing the demographic structure and body condition of tuatara populations on three islands before and after removal of rats and on a fourth island where rats remained. In the presence of rats, juvenile tuatara constituted on average 0–5% of the sample tuatara populations. When Pacific rats were removed after at least 200 years' occupancy, the proportion of juvenile tuatara increased 3.5‐ to 17‐fold and body condition of adult males and females also improved (sometimes dramatically). We predict that, unless Pacific rats are removed from Taranga Island, the tuatara population will collapse because of low population density and the lack of juvenile recruitment. Our results demonstrate that when invasive species exert subtle effects on recruitment and body condition, the effects on populations of long‐lived endemic species may only become apparent long after the invasion.

Frequent Tanning Bed Use, Weight Concerns, and Other Health Risk Behaviors in Adolescent Females (United States) - David L. O’Riordan; Alison E. Field; Alan C. Geller; Daniel R. Brooks; Gideon Aweh; Graham A. Colditz; A. Lindsay Frazier (Cancer Causes & Control, 2006)

Maximal voluntary hyperpnoea increases blood lactate concentration during exercise - Michael A. Johnson; Graham R. Sharpe; Alison K. McConnell (European Journal of Applied Physiology, 2006)

The effect of inspiratory muscle training upon maximum lactate steady-state and blood lactate concentration - Alison K. McConnell; Graham R. Sharpe (European Journal of Applied Physiology, 2005)

Non-coordinate expression of peroxisome biogenesis, ?-oxidation and glyoxylate cycle genes in mature Arabidopsis plants - Wayne L. Charlton; Barbara Johnson; Ian A. Graham; Alison Baker (Plant Cell Reports, 2005)

Resource competition and adaptive radiation in a microbial microcosm - R. Craig MacLean; Alison Dickson; Graham Bell (Ecology Letters, 2005)
Theory predicts that competition for shared resources in a monomorphic population generates divergent selection for adaptation to alternative resources. Experimental tests of this hypothesis are scarce. We selected populations of the bacterium Pseudomonas fluorescens in spatially homogeneous microcosms containing a complex mixture of resources. Initially, all populations consisted of two isogenic clones. The outcome of selection was the evolution of a diverse community of genotypes within each population. Sympatric genotypes exhibited differentiation in metabolic traits related to resource acquisition and frequency‐dependent trade‐offs in competitive ability, as we would expect if different genotypes consumed different resources. These results are consistent with the hypothesis of adaptive radiation driven by resource competition. Reconciling the results of this study with those of earlier experiments provides a new interpretation of the ecological causes of adaptive radiation in microbial microcosms.

Upregulation of cAMP-specific PDE-4 activity following ligation of the TCR complex on thymocytes is blocked by selective inhibitors of protein kinase C and tyrosyl kinases - Alison M. Michie; Graham Rena; Margaret M. Harnett; Miles D. Houslay (Cell Biochemistry and Biophysics, 1998)